PERANCANGAN BUKU RESEP 30 IKON KULINER TRADISIONAL INDONESIA UNTUK GENERASI MUDA - CAROL NATHALIE SERENAMI; RENE ARTHUR PALIT (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2017)
Indonesia is an archipelago witha high diversity. As a country with various cultural aspects, Indonesia inherits the most diverse traditional dishes. It is estimated that there are over 5,000 kinds of Indonesian dishes. In 2012 the Indonesian government, through the Ministry of Tourism and Creative Economy (Kemenparekraf), has launched 30 culinary icons that best represent Indonesia's best culinary assets. The recipes of the 30 Indonesian culinary icons and their complicated cooking stages need to be documented into a handbook. This handbook will indirectly introduce the culinary of Indonesia more broadly, even internationally.Â Influenced by the modern lifestyle, the Indonesian younger generation is currently more interested in the culinary of foreign countries rather than the local one. They have not admitted the Indonesian cuisine as their pride. Some books that introduce 30 Indonesian culinary icons have been published, but to further enrich the literature, another book about 30 Indonesian culinary icons is designed with styles and visuals different from the previous ones. The book is designed in a journal style to resemble a cooking record, with the incorporation of illustrations and photography. The design is also equipped by supporting medias such as booklets, websites, social media accounts, and the medias neededfor book launching. It is expected that through this design, the younger generation will become more interested and proud of Indonesia's unique cuisine as one of the cultural heritage.Keywords: culinary icon; illustration; indonesia; recipe book; young generation.